Suppression of the T-dependent antibody response following oral exposure to selected polycyclic aromatic compounds in B6C3F1/N mice - Johnson, Victor J.; Rider, Cynthia V.; Luster, Michael I.; Willson, Cynthia J.; Harris, Shawn; Stiffler, Billie; Blake, James; Mutlu, Esra; Godfrey, Veronica; Burback, Brian; Fernando, Reshan; Waidyanatha, Suramya; et al. (Frontiers in Toxicology, 2025)
IntroductionThe ability of polycyclic aromatic compounds (PACs), most notably benzo(a) pyrene [B(a)P], to suppress antibody responses in experimental animals is well documented. Very little information, however, is available on the immunotoxicity of related PACs despite their widespread presence in the environment. Additionally, there are several weaknesses in existing immunotoxicity databases for PACs in experimental animals, limiting their applicability in quantitative risk assessment. Careful characterization of strong positive and clear negative PACs is needed in order to lay the foundation for generating robust immunotoxicity data for structurally diverse PACs that have not yet been evaluated.MethodsIn the current study, adult B6C3F1/N female mice were treated daily for 28 consecutive days by oral administration of B(a)P to provide dose levels ranging between 2 and 150 mg/kg bodyweight/day. In addition, phenanthrene and pyrene, non-carcinogenic PACs, were tested at dose ranges between 12.5 and 800 mg/kg bodyweight/day and 3.1 and 200 mg/kg bodyweight/day, respectively. Immune assessments following PAC exposure included organ weights and immunopathology, hematology, quantification of immune cell types in the spleen, and T-dependent antibody response (TDAR) to sheep red blood cells (SRBC).ResultsBenzo(a)pyrene exposure resulted in significant decreases in lymphoid organ weights, immune cell populations in the spleen and TDAR. The most sensitive indicator for immunotoxicity from B(a)P treatment was suppression of antibody responses, where an ∼75% decrease occurred at a dose level of 9 mg/kg bodyweight/day and ∼32% decrease at the lowest tested dose of 2 mg/kg bodyweight/day. Antibody suppression was associated with significant immune cell loss in the spleen; however, it was clear that the suppression of the TDAR was more sensitive than cell loss indicating that cell function impairments were involved. Phenanthrene treatment also resulted in suppression of the antibody response but only at dose levels ≥50 mg/kg bodyweight/day without significant effects on other parameters, while pyrene showed no significant immune effects.ConclusionSuppression of the TDAR to SRBC immunization was the most sensitive immune endpoint being 33 times more sensitive than changes in liver weight, a commonly used outcome for risk assessment for PACs. Benzo(a)pyrene was the most potent PAC regarding suppression of humoral immunity whereas pyrene did not affect the immune responses tested. These studies lay the foundation for evaluating diverse PACs with a range of immunotoxicological potencies.